Anal Canal Carcinoma in a Child With Disorders of Sex Development. Issue 7 (1st April 2016) - Watanabe, Toshihiko; Horikawa, Reiko; Masaki, Hidekazu; Yoshioka, Takako; Matsumoto, Kimikazu; Kanamori, Yutaka
Abstract : Squamous cell carcinoma of the anal canal in children is rare. To date, the etiology and outcome of this condition have been not fully understood. Here, we report an 11‐year‐old child with anal canal cancer who had concomitant disorders of sex development. Radiotherapy followed by salvage surgery achieved disease‐free survival of 3 years. Since overexpression of cell cycle regulatory protein p16 was immunohistochemically evident in tumor tissue, human papillomavirus infection was considered as a causative factor in the carcinogenesis.